Curiosity-Driven Learning in Arabic: A Case Study on the 'Inquiring Minds Want to Know' Approach - dewi, intan; Ahmad Nurcholis; Izzatul Laila; Juan Acevedo; Moumen El-Sayed (IAIN Madura, 2025)
This study aims to analyze the implementation of the